AWS certified advanced networking official study guide specialty exam - Chauhan, Sidhartha (Sybex/John Wiley & Sons, Inc., 2018)
The AWS Certified Advanced Networking Official Study Guide - Specialty Exam helps to ensure your preparation for the AWS Certified Advanced Networking - Specialty Exam. You also get one year of free access to Sybex's online interactive learning environment and study tools, which features flashcards, a glossary, chapter tests, practice exams, and a test bank to help you track your progress and gauge your readiness as exam day grows near.